The art and culture of Japan - Delay, Nelly (New York : Harry N. Abrams, 1999)
Text and many color photos profile several strains of historical Japanese art and culture, covering the "kami," the Buddhist tradition, the court, the warrior, Zen, and the Edo period; also includes a section of related documents, a chronology, and a bibliography.
Includes bibliographical references (p. 153) and index.
Keywords: Japan -- Civilization